2014
DOI: 10.1155/2014/345941
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Efficacy of Group Medical Nutrition Therapy and Motivational Interviewing among Obese African American Women with Type 2 Diabetes: A Pilot Study

Abstract: Objective. To assess the efficacy and acceptability of a group medical nutritional therapy (MNT) intervention, using motivational interviewing (MI). Research Design & Method. African American (AA) women with type 2 diabetes (T2D) participated in five, certified diabetes educator/dietitian-facilitated intervention sessions targeting carbohydrate, fat, and fruit/vegetable intake and management. Motivation-based activities centered on exploration of dietary ambivalence and the relationships between diet and perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Experimental studies find that changes in choice architecture can successfully promote certain behaviors within areas such as eating, but that individuals tend to deny being influenced by choice architecture while suggesting that other people are affected [4, 37]. This way of dissociating between oneself and others might also be related to a tendency to assess own health status and behavior in a favorable light [38, 39]. These findings are in agreement with our findings of the modest intervention awareness and the great belief in how the checkout intervention could be helpful to other consumers not least to those with children nagging for confectionery.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies find that changes in choice architecture can successfully promote certain behaviors within areas such as eating, but that individuals tend to deny being influenced by choice architecture while suggesting that other people are affected [4, 37]. This way of dissociating between oneself and others might also be related to a tendency to assess own health status and behavior in a favorable light [38, 39]. These findings are in agreement with our findings of the modest intervention awareness and the great belief in how the checkout intervention could be helpful to other consumers not least to those with children nagging for confectionery.…”
Section: Discussionmentioning
confidence: 99%
“…The potential public health consequences of the misperception of BMI and the inability to recognise obesity in oneself have also been the subject of much discussion [2327]. In particular, Duncan et al [23] have shown that the misperception of BMI among overweight and obese adults was associated with less likelihood of interest in, or attempts at, weight loss, and less physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies discussed above [1420, 27], we hypothesised that body weight is underestimated for a complete population for multiple perception questions and that an intervention from a medical professional can cause a substantial change in self-perception.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies Diabetes Care/Services in African American Women -Miller et al diabetes-related microvascular and macrovascular complications (HbA1c ≥ 7.0%, and either systolic blood pressure of ≥130 mm Hg, LDL cholesterol ≥100, or BMI ≥30). As part of group-based dietary self-care 12 and weight management interventions, participants were recruited using managed care organization referrals and radio, email, flyer and church advertisements. Study protocol was approved by the Meharry Medical College institutional review board.…”
Section: Discussionmentioning
confidence: 99%